Influence of rumen bypass fat fed with total mixed ration on growth performance in Nili-Ravi buffalo calves - AHMED, S.; AAMIR, M.; UL-HAQUE, M. N.; AHMAD, N.; MARGHAZANI, I.B.; KHAN, M. I. (Journal of the Hellenic Veterinary Medical Society, 2021)
This study was conducted to know the influence of rumen bypass fat supplement on growth performance of Nili-Ravi mal buffalo calves. Nili Ravi buffalo male calves (n=12) were randlomly selected and divided into two groups i.e., A and B based on two different levels of age. These groups (A and B) were further divided into two respective subgroups i.e., A1, A2 and B1, B2. Sub groups A1 and BI served as control (without supplement) whilst subgroups A2 and B2 were fed RBF supplement (at the rate of 2.35% of dry matter intake) with basel diet with total mixed ration. Results showed no statistical difference (P>0.05) in dry matter intake, body weight gain and body condition score on rumen bypass fat supplementation. In blood metabolites, rumen bypass fat supplementation increased (P<0.05) blood triglyceride and cholesterol levels, however, it reduced (P<0.05) blood glucose level in Nili-Ravi buffalo male calves. This study suggests that supplementation of rumen bypass fat at the rate of 2.35% per day in TMR possess no impact on growth performance parameters in Nili Ravi buffalo male calves.